2013
DOI: 10.1016/j.ejpb.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Drug release kinetics, cell uptake, and tumor toxicity of hybrid VVVVVVKK peptide-assembled polylactide nanoparticles

Abstract: An exciting approach to tumor delivery is encapsulation of the drug in self-assembled polymer-peptide nanoparticles. The objective of this work was to synthesize a conjugate of low molecular weight polylactide (LMW PLA) and V6K2 peptide, and investigate self-assembly, drug release kinetics, cell uptake and toxicity, drug pharmacokinetics, and tumor cell invasion with Doxorubicin (DOX) or paclitaxel (PTX). The results for PLA-V6K2 self-assembled NPs were compared with those of polyethylene glycol stabilized PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 91 publications
0
29
0
Order By: Relevance
“…The number of peptides in a peptide/lactidecapped PEG conjugate was determined using the acrylate/ PEG molar ratios before and after conjugation as previously described. 28 The average number of peptides per conjugate for L0, L2, L4, and L6 macromers was 0.57, 0.49, 0.52, and 0.45, respectively. Several studies have demonstrated that >95% of acrylated PEG/peptide conjugates are integrated in PEGDA hydrogel network during photocrosslinking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of peptides in a peptide/lactidecapped PEG conjugate was determined using the acrylate/ PEG molar ratios before and after conjugation as previously described. 28 The average number of peptides per conjugate for L0, L2, L4, and L6 macromers was 0.57, 0.49, 0.52, and 0.45, respectively. Several studies have demonstrated that >95% of acrylated PEG/peptide conjugates are integrated in PEGDA hydrogel network during photocrosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…25,28 The number of lactide repeat units per chain end of the lactide-capped PEG macromer was determined from the ratio of the peaks at 1.6 and 5.2 ppm (lactide hydrogens) to those at 3.6 and 4.3 ppm (PEG hydrogens). 25 The average number of lactide repeat units per chain end for L2, L4, and L6 macromers was 1.9, 3.6, and 5.6, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the experiments have demonstrated that the PLA-V6K2 nanoparticles conjugated with anticancer drugs have higher toxicity to cancer cells and no toxicity to normal cells compared with free doxorubicin or paclitaxel and pure PLA nanoparticles conjugates. Therefore, this study demonstrated the higher efficacy of these PLA-V6K2 nanoparticles for anticancer drug delivery that could be potentially useful in cancer therapy [123].…”
Section: Anticancer Drug Deliverymentioning
confidence: 99%
“…In this study, we have explored new thermoresponsive polymeric micelles (Ward and Georgiou, 2011;Dhar et al, 2011;Jabbari et al, 2013) PNIPAAm-VP to overcome some of the limitations of currently available polymer micelles. The objectives of this work were to synthesize PNIPAAm-VP nanoparticles and to study the efficacy enhancement on cancer cell lines MCF-7 and B16F0 and size distribution properties of the particles.…”
Section: Introductionmentioning
confidence: 99%